(untitled) (World Bulletin of Education and Learning, 2025)
This article examines the historical roots, musical structure, and performance traditions of the Uzbek maqom Navo, one of the most distinguished pieces in the Shashmaqom cycle. The study explores both the instrumental and vocal sections of the maqom, focusing on their rhythmic and modal organization, as well as performance practices preserved through the ustoz–shogird (master–apprentice) tradition. Navo maqom embodies profound philosophical and spiritual meanings, representing emotional purification and divine inspiration in the context of classical Uzbek music. The article also integrates theoretical and practical perspectives from recent scholarship to provide a comprehensive understanding of the artistic and cultural significance of this maqom.